Theoretical Foundation of Dialectics of Economic Development in Karl Marx’s Capital - Dyatel, Evgeny Petrovitch (Economy of Regions, 2018)
The article deals with the logical and theoretical structure of K. Marx’s «Capital». In the «Theories of Surplus Value», there is the ascent from the concrete to the abstract in the history of economic thought. This ascent allowed to define the goods as a starting point for the political economy of the capitalist mode of production. But there is no direct way to the economic theory of Marx, whose subject is not the products labour activity, but the material production relations arising during these activities. While researching the goods, Marx uses the «power of abstraction», which allows separating «economic matter» from the «naturally tangible» material basis: use value, concrete labour, etc. An integral system of economic categories is based on the synthesis of natural historical thinking phenomena discovered by Aristotle; Hegel’s understanding of purposive activity; specific goals of social production, which are realized in property relations. K. Marx introduces into scientific knowledge the notion of economic progress as a change of social formations. He considers the significance of different models of the division of labour for determining the concept of value. In A. Smith’s model, the value is determined a posteriori, after market evaluation of the products or services produced. A unit of measurement is not working time in itself, but economic information on the effectiveness of its use, i.e. money. In the model of K. Marx, the value is determined a priori, in the form of labour costs in the physiological sense. Given a choice, the labour expended receives a marginal evaluation in the form of alternative costs (loss of profits). The meaning of the «absolute, universal law of capitalist accumulation» is identified as a causa finalis, which determines the value of the commodity labour, variable capital, surplus value. I conclude that the development of the dialectics of the topic and the focus of an economic study allows using the method of rational eclecticism if the corresponding material is subject to a subsequent dialectical-materialistic interpretation.